2016
DOI: 10.4103/2277-9175.176368
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between non-alcoholic fatty liver disease and inflammation in patients with non-alcoholic fatty liver

Abstract: Background:Non-alcoholic fatty liver is the most chronic liver disease that eventually can become cirrhosis. One of the underlying assumptions for the fatty liver created by inflammation of the hepatocytes. We aimed to assess the association between non-alcoholic fatty liver disease (NAFLD) and sub-clinical inflammation.Materials and Methods:This is a cross-sectional study which was conducted on 55 patients over 30 years, with NAFLD. Fatty liver grade was assessed using liver ultrasound. Liver enzymes (alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 28 publications
5
18
0
Order By: Relevance
“…Suggested mechanisms resulting in increased hemoglobin levels are hepatic hypoxia, oxidative stress, formation of reactive oxygen species and lipid peroxidation[ 37 , 39 ]. The association of (subclinical) elevated inflammatory markers and the presence of NAFLD has also been reported in other studies[ 40 ]. This may be explained by increased visceral adipose tissue conferring a pro-inflammatory state[ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 74%
“…Suggested mechanisms resulting in increased hemoglobin levels are hepatic hypoxia, oxidative stress, formation of reactive oxygen species and lipid peroxidation[ 37 , 39 ]. The association of (subclinical) elevated inflammatory markers and the presence of NAFLD has also been reported in other studies[ 40 ]. This may be explained by increased visceral adipose tissue conferring a pro-inflammatory state[ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 74%
“…In our study, subjects in the NAFLD group presented with signi cantly higher CRP levels. This nding is consistent with the results reported from earlier studies where a positive correlation been CRP and NAFLD have been demonstrated [27]. Furthermore, subjects in the NAFLD group had higher Charlson comorbidity index scores, lower albumin levels and higher GGT levels which are all predictors of short-term and longterm mortality [16,28,29].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, high level of CRP was also used for the prediction of metabolic syndrome, T2DM, and coronary heart disease [46,47]. Despite the controversial opinions, there are still several studies identified the association between high levels of CRP and NAFLD [48][49][50]. In this study, liraglutide was more effective than metformin at decreasing the levels of CRP.…”
Section: Discussionmentioning
confidence: 78%